2015
DOI: 10.1016/j.jacc.2015.09.079
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Wearable Cardioverter-Defibrillator in Patients With Newly Diagnosed Cardiomyopathy

Abstract: In this independent, retrospective study, the risk of appropriate WCD therapies in patients with newly diagnosed NICM was minimal. Routine use of the WCD in this population should be prospectively evaluated. The risk of appropriate therapies in newly diagnosed ICM was comparable to that observed in prior observational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 18 publications
3
41
2
2
Order By: Relevance
“…44,45 In a single-center series of 254 NICM patients prescribed WCD use over a period of 10 years, no patients received an appropriate shock. 46 Another study involving a mixed patient population who qualified for WCD use showed that only 2.7% of arrhythmias lasted more than 25 seconds, and that the majority of them were self-terminating. The rate of appropriate shocks was 1.58 per 100 patient-months, and the rate of inappropriate shocks was 0.99 per 100 patient-months.…”
Section: Wearable Cardiac Defibrillatorsmentioning
confidence: 99%
“…44,45 In a single-center series of 254 NICM patients prescribed WCD use over a period of 10 years, no patients received an appropriate shock. 46 Another study involving a mixed patient population who qualified for WCD use showed that only 2.7% of arrhythmias lasted more than 25 seconds, and that the majority of them were self-terminating. The rate of appropriate shocks was 1.58 per 100 patient-months, and the rate of inappropriate shocks was 0.99 per 100 patient-months.…”
Section: Wearable Cardiac Defibrillatorsmentioning
confidence: 99%
“…The more recent prospective WEARIT-II registry [8] showed a 1% VT/VF event rate in 922 patients with newly diagnosed DCMP within 3 months of WCD therapy. A single center experience [10] reported no shocks for VT/VF in 271 patients with newly diagnosed non-ischemic cardiomyopathy during a median wear time of 71 days. Reversibility of the cardiomyopathy processes, as well as early improvement in LV function with vigorous pharmacological therapy, may explain the low incidence of VT/VF in this patient population, and suggests that the addition of short-term therapy with the WCD may have limited, if any, effect on overall survival.…”
mentioning
confidence: 99%
“…It has been marketed for use in patients deemed at elevated risk of SCD from ventricular arrhythmias in whom a permanent ICD is either contraindicated or under consideration. To date, there have been several publications describing its use in clinical registries [5,6], national experiences [4,7], and single-center studies [8], primarily as a short-term means of mitigating risk while patients undergo more comprehensive evaluation or titration of medical therapy. There are, at present, no currently published randomized WCD clinical trials demonstrating a mortality benefit.…”
mentioning
confidence: 99%
“…On a psychosocial level, wearing the WCD consistently for a year requires tremendous personal fortitude. If one assumes a monthly fee of $3000 for the WCD [8], its cost over 1 year is similar to an ICD, yet after that year, additional protection against SCD will require additional financial input.…”
mentioning
confidence: 99%
See 1 more Smart Citation